Tinjauan Al-Ghazālī terhadap Ilmu Kalam dan Pendekatan Berargumen dalam Kitab Al-Iqtiṣād Fī Al-I’tiqād - Iqbal Nursyahbani; Ahmad Nurhamdani; Fahmi Husen; Mohammad Farid (Attractive : Innovative Education Journal, 2024)
All-Ghazali is one of the Muslim intellectuals who is very persistent in fighting against deviant understanding in Kalam science. One of his works is the book al-Iqtiṣād fi al-I'tiqād, the introduction to the book contains al-Ghazali's attitude and review in Kalam science as well as his argumentative methodology in Kalam science. So this feels necessary to be expressed. For this reason, this research is present to reveal al-Ghazali's review and methodology in his book. Therefore, this study focuses on content analysis methods and describes those contained in the introduction to the book al-Iqtiṣād fi al-I'tiqād. It can be concluded that al-Ghazali had a view of how important the science of Kalam was, so that al-Ghazali divided humans into four groups even though deepening it was only mandatory for certain people. And al-Ghazali has three methods in arguing, namely, as-Sabru wat Taqsim, Qiyas Hamli, and explaining that the opponent's argument is wrong.